ANALISIS DAN IMPLEMENTASI SISTEM KEAMANAN JARINGAN KOMPUTER DENGAN METODE INTRUSION DETECTION SYSTEM (STUDI KASUS: HORISON ULTIMA RISS HOTEL) - Catur Iswahyudi; Agradira Dwi Wahyuda; Erfanti Fatkhiyah (IST AKPRIND Yogyakarta, 2018)
Ultima Riss Horizon Hotel has applications and documents requiring network connections to be accessed online by both hotel staff and visitors. For security reasons, Ultima Riss Horizon Hotel requires a system to secure transaction data and other documents. The threat encountered is an intruder trying to take control of the server using root access to the company's central database server. One solution to this problem is to apply the Intrusion Detection System (IDS) method to maintain system security that can detect and reduce the risk of computer network security intrusions from intruders. This study aims to improve network security at Horison Ultima Riss Hotel by creating a monitoring system that can provide information in case of an attack on the network system. The method used is IDS approach using Snort, firewall, and other applications. Furthermore, an analysis of the reports generated by IDS Snort and the firewall as a precaution prior to the attack. The test results show that the firewall and IDS Snort capable of recording activities suspected of being a threat of disruption to the network and analyze the packets based on existing rules to recognize the existence of an attack attempt from the intruder.